The middle sort of people in provincial England, 1600-1750 - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2009)
French’s study of the middling sorts in England seeks to explore the origins and role ofthe ‘middling sorts’ in the social and economic culture of the early modern period. Hisresearch focuses on parochial and extra-parochial perceptions of middling socialidentity based on a series of case studies across a broad area, including Dorset, Essex,Suffolk and Lancashire. The purpose of such a wide geographical spread is to explorethe development of the middling sorts in regions of diverse agriculture, economy andindustry as a basis for a comparative survey.